Routledge philosophy guidebook to Rousseau and the social contract - Bertram, Christopher, 1958- (Routledge, 2004)
Rousseau's Social Contract is a benchmark in political philosophy that has inspired and influenced moral and political thought since publication and is widely studied for this reason.
Keywords: Rousseau, Jean-Jacques, -- 1712-1778. -- Du contrat social.; Du contrat social (Rousseau, Jean-Jacques); Rousseau, Jean-Jacques -- 1712-1778.; Rousseau, Jean-Jacques (1712-1778). -- Du contrat social.; Rousseau, Jean-Jacques, -- (1712-1778); Rousseau, Jean-Jacques, -- 1712-1778.; Rousseau, Jean-Jacques <1712-1778>; Rousseau, Jean-Jacques.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; POLITICAL SCIENCE -- Essays.; Gesellschaftsvertrag.; Du contrat social ou Principes du droit politique (Rousseau); Contrat social.; État.; Philosophie politique.; Théorie politique.